A Better Understanding of the Formation of Silica Nanococoons - 许臻 赵环宇 闫卓君 王思兵 陈媛丽 李宝宗 李艺 杨永刚 (Chinese journal of chemistry, 2011)
Silica nanococoons with coiled or concentric circular pore channels in the walls attracted much attention, recently. However, the formation of them is not well illustrated. Herein, hollow silica shells with organized pore channels parallel to the shell surface were prepared through a single-templating method using the self-assemblies of a chiral low-molecular-weight amphiphile, L-18Phe6PyBr, as templates under a dilute concentration. These nano- cocoons were characterized using X-ray diffractometer and N2 sorption. The formation of them was clearly shown in the field-emission electron microscopy images which were taken at a low voltage. Moreover, transmission elec- tron microscopy images taken after different reaction times indicated a cooperative self-assemble mechanism. It was also found that the nanocoons were formed from coiled nanoribbons.